Phagocytic Index of Peritoneal Macrophages after Propolis Suplementation in Mice (Mus musculus) - Mustafiah, Siti Eva; Fatmawati, Dina; Yusuf, Iwang (Fakultas Kedokteran; Universitas Islam Sultan Agung (UNISSULA), 2011)
Background: Various diseases depend on individual’s immunity. Many of which nowadays have not had the effective and formal therapy that makes experts researches the best and the most effective way for it; the use of Propolis as immunomodulator is one of them. This research aims for knowing the effect of propolis towards peritoneal macrophage phagocytic index on mice.Design and Method: This research is an experiment with post test study design randomized control group design. This study used mice that were divided into four groups randomly. The first group / Group-I were for negative control (standard feed and aquadest); The second group/Group-II were fed standard-feed, aquadest, and propolis at a dose of 1.25 mg/kgBM; the third group/group-III were fed standard-feed, water, and propolis at a dose of 2.5 mg/KgBM; The fourth group/Group-IV were fed standard feed, water, and propolis at a dose of 5 mg/KgBM. Treatment where conducted for 3 days.Result: The average macrophage phagocytic index, were at the highest level of it (7.82 1.63) while the lowest one were the first group 3.43 0.13. The Kruskall Wallis result stated that there is index difference among various groups with p 0.002 (p < 0.05).Conclusion: Propolis effected on mice peritoneal macrophage phagocytosis index (Sains Medika, 3(2):121-128).